The Relationship of Chlorophyll-A to Mackerfish Captures In The Waters of Ternate City - Syahnul Sardi Titaheluw; Rovina Andriani; Aisyah Bafagih; Ibnu Laitupa (Journal of Global Sustainable Agriculture, 2022)
Chlorophyll-a is an indicator of the abundance of phytoplankton in waters which plays a role in the process of photosynthesis. Phytoplankton plays a crucial role in determining primary productivity in waters. Organic carbon production during photosynthesis is defined as direct or net primary productivity (Net Primary Productivity). Ternate Island waters are part of the province of North Maluku and as one of the waters that play a vital role in contributing to the production of capture fisheries, especially pelagic and demersal fish. This research was carried out from January to June 2020, located in the waters of the City of Ternate. This research data was obtained by downloading the detected image/Aqua MODIS. This image data is available on the internet (http://oceancolor.gsfc.nasa.gov).